Interrelation of individual-personal qualities and dynamics of functional states participants of the sea Arctic expedition - M. A. Tunkina; Ya. A. Korneeva; N. N. Simonova; A. A. Trofimova (Acta Biomedica Scientifica, 2022)
The issues of psychological adaptation of a person to the extreme conditions of the Arctic continue to be relevant at the present time. Dynamic monitoring of human functional states is an effective technology that allows timely identification of the level of human adaptation to the conditions of the North and implementation of preventive measures to maintain health in extreme working conditions.   The aim of the study is to identify and describe the relationship of individual-personal qualities and the dynamics of the functional states of the participants of the marine Arctic expedition.   Methods. Psychophysiological testing using the device UPFT-1/30-«Psychophysiolog» (variational cardiointervalometry, complex visual-motor reaction); color preference test (M. Luscher, adapted by L. N. Sobchik) with calculation of interpretation coefficients by G. A. Aminev; Five-factor personality questionnaire (R. McCrae and P. Costa, adapted by A. B. Khromov); statistical methods: descriptive statistics, frequency analysis, correlation analysis using Spearman’s rank correlation coefficient. The study was conducted daily in the morning and evening for 20 days on the research vessel Mikhail Somov in June 2021. The study involved 39 people, including participants in the scientific and educational expeditionary project “Arctic Floating University–2021”.   Results. The dynamics of psychophysiological and projective psychological parameters of the functional states of the expedition members as a whole is characterized by favorable levels, which indicates their adaptation to the conditions of high latitudes. According to the results of the correlation analysis, statistically significant relationships were revealed between the dynamics of functional states and such individual-personal qualities as: extraversion − introversion and attachment − separation.   Conclusion. The results of the study are consistent with the data of previous expeditions of the “Arctic floating university” and other polar expeditions. The revealed interrelations of functional states with different personality characteristics of the participants testify in favor of the complex nature of the study using different groups of diagnostic methods.